Efficacy evaluation of combination vaccine of recombinant C-terminal fragments of ApxIA, ApxIIA and ApxIIIA in piglets - Moon, Ja Yong Moon; Kang, Ji Young; Seo, Jeong-Woo; Kim, Won Kyong; Choi, Yeong Hwan; Choi, Min Soo; Hur, Jin (Penerbit Universiti Kebangsaan Malaysia, 2017)
The efficacy of the combination vaccine of the individual C-terminal fragments of ApxIA, ApxIIA and ApxIIIA of Actinobacillus pleuropneumoniae (APP) was evaluated in piglets. Twenty piglets were divided equally into 2 groups (n=10). All piglets were intramuscularly primed at 4 week-of-age (0 week post prime inoculation (WPPI)) and were intramuscularly boosted at 6 week-of-age (2 WPPI). Group A piglets were inoculated with sterile PBS and group B piglets were inoculated with the combination vaccine. Concentrations of each of the C-terminal fragment-specific IgG as determined by ELISA were significantly higher in group B than in group A from 2 WPPI until the end of this study. Clinical signs were observed from only 10% of group B piglets after the challenge with the mixture of APP serotypes 1, 2 and 5 at 4 WPPI, while 50% of group A piglets were protected against APP infections. Overall, intramuscular inoculation with the vaccine candidate can efficiently protect piglets against APP infection.